Cholesterol regulation of mechanosensitive ion channels - Beverley, Katie M.; Levitan, Irena (Frontiers in Cell and Developmental Biology, 2024)
The purpose of this review is to evaluate the role of cholesterol in regulating mechanosensitive ion channels. Ion channels discussed in this review are sensitive to two types of mechanical signals, fluid shear stress and/or membrane stretch. Cholesterol regulates the channels primarily in two ways: 1) indirectly through localizing the channels into cholesterol-rich membrane domains where they interact with accessory proteins and/or 2) direct binding of cholesterol to the channel at specified putative binding sites. Cholesterol may also regulate channel function via changes of the biophysical properties of the membrane bilayer. Changes in cholesterol affect both mechanosensitivity and basal channel function. We focus on four mechanosensitive ion channels in this review Piezo, Kir2, TRPV4, and VRAC channels. Piezo channels were shown to be regulated by auxiliary proteins that enhance channel function in high cholesterol domains. The direct binding mechanism was shown in Kir2.1 and TRPV4 where cholesterol inhibits channel function. Finally, cholesterol regulation of VRAC was attributed to changes in the physical properties of lipid bilayer. Additional studies should be performed to determine the physiological implications of these sterol effects in complex cellular environments.